Mineral Composition of Four Edible Mushrooms - S. E. Mallikarjuna; A. Ranjini; Devendra J. Haware; M. R. Vijayalakshmi; M. N. Shashirekha; S. Rajarathnam (Journal of Chemistry)
Two cultivated mushroom species, namely, Lentinula edodes and Pleurotus florida and two wild growing species Lentinus cladopus and Pleurotus djamor were studied for their mineral contents such as Ca, Mg, Na, K, Fe, Zn, Mn, Cu, Ni, Se, Pb, and Cd by Inductive Coupled Plasma Atomic Emission Spectroscopy (ICP-AES) and also Atomic Absorption Spectroscopy, (AAS). Phosphorus was estimated by spectrophotometric method. K, Ca, Na, and P were in higher concentrations ranging from 59.3 mg to 3634 mg, 8.27 mg–174.9 mg, 22.2 mg–327.4 mg, and 100.5 mg–769.9 mg/100 g dry weight respectively in the four mushroom species studied. Fe, Zn, Mg and Se were ranging from 6.27 mg to 35.3 mg, 1.58 mg–9.44 mg, 21.1 mg–40.7 mg and 0.048 mg–0.182 mg/100 g dry weight, respectively, amongst the mushroom species analyzed. However, Ni, Cu, and Mn contents showed relatively lower concentrations, whereas Pb and Cd were below detectable level. The mushrooms were safe for consumption, in accordance with the permissible tolerance limits of the estimated toxic metals. Implications of the mineral contents on mushroom nutritional value are highlighted.